Mammalian GCN5 and P/CAF Acetyltransferases Have Homologous Amino-Terminal Domains Important for Recognition of Nucleosomal Substrates - Wanting Xu; Diane G. Edmondson; Sharon Y. Roth (1998)
The yeast transcriptional adapter Gcn5p serves as a histone acetyltransferase, directly linking chromatin modification to transcriptional regulation.Two human homologs of Gcn5p have been reported previously, hsGCN5 and hsP/CAF (p300/CREB binding protein [CBP]-associated factor).While hsGCN5 was predicted to be close to the size of the yeast acetyltransferase, hsP/CAF contained an additional 356 amino-terminal residues of unknown function.Surprisingly, we have found that in mouse, both the GCN5 and the P/CAF genes encode proteins containing this extended amino-terminal domain.Moreover, while a shorter version of GCN5 might be generated upon alternative or incomplete splicing of a longer transcript, mRNAs encoding the longer protein are much more prevalent in both mouse and human cells, and larger proteins are detected by GCN5-specific antisera in both mouse and human cell extracts.Mouse GCN5 (mmGCN5) and mmP/CAF genes are ubiquitously expressed, but maximum expression levels are found in different, complementary sets of tissues.Both mmP/CAF and mmGCN5 interact with CBP/p300.Interestingly, mmGCN5 maps to chromosome 11 and cosegregates with BRCA1, and mmP/CAF maps to a central region of chromosome 17.As expected, recombinant mmGCN5 and mmP/CAF both exhibit histone acetyltransferase activity in vitro with similar substrate specificities.However, in contrast to yeast Gcn5p and the previously reported shorter form of hsGCN5, mmGCN5 readily acetylates nucleosomal substrates as well as free core histones.Thus, the unique amino-terminal domains of mammalian P/CAF and GCN5 may provide additional functions important to recognition of chromatin substrates and the regulation of gene expression.